Effects of different nitrogen forms on cadmium accumulation of Sedum alfredii Hance - LI Ji-guang; LI Ting-qiang; ZHU En; YANG Xiao-e (浙江大学学报. 农业与生命科学版)
The effects of nitrogen form on plant growth and cadmium (Cd) accumulation in two ecotypes Sedum alfredii Hance were investigated using hydroponic culture. The results show that biomass (dry matter) of shoots and chlorophyll a, b content of hyperaccumulating ecotype (HE) increased markedly when plants were supplied with (NH4)2SO4, Ca (NO3)2 and NH4NO3, but the increase was greater with the treatment of (NH4)2SO4 under either low (10 μmol·L-1) or high Cd (100 μmol·L-1) level. Cadmium concentrations in the shoots of both ecotypes Sedum alfredii Hance were not significantly affected by the treatments of (NH4)2SO4, Ca (NO3)2 and NH4NO3, whereas the root Cd concentrations increased to a certain extent. Cadmium amount accumulated in the shoot and root of both ecotypes of Sedum alfredii Hance increased significantly when plants were supplied with different nitrogen form, as for hyperaccumulating ecotype treated with (NH4)2 SO4, cadmium accumulation increased more than those treated with Ca (NO3)2 and NH4NO3. Results above indicated that NH4+-N has greater ability to promote Cd accumulation in Sedum alfredii Hance than NO3--N, and the application of (NH4)2SO4 may be useful approach to enhance the Cd accumulation in hyperaccumulating ecotype Sedum alfredii Hance for phytoremediation of the Cd-contaminated soil.